Real-world evidence on non-invasive tests and associated cut-offs used to assess fibrosis in routine clinical practice - YILMAZ, YUSUF (My University, 2022)
© 2022 The Author(s)Background & Aims: Non-invasive tests (NITs) offer a practical solution for advanced fibrosis identification in non-alcoholic fatty liver disease (NAFLD). Despite increasing implementation, their use is not standardised, which can lead to inconsistent interpretation and risk stratification. We aimed to assess the types of NITs and the corresponding cut-offs used in a range of healthcare settings. Methods: A survey was distributed to a convenience sample of liver health experts who participated in a global NAFLD consensus statement. Respondents provided information on the NITs used in their clinic with the corresponding cut-offs and those used in established care pathways in their areas. Results: There were 35 respondents from 24 countries, 89% of whom practised in tertiary level settings. A total of 14 different NITs were used, and each respondent reported using at least one (median = 3). Of the respondents, 80% reported using FIB-4 and liver stiffness by vibration-controlled transient elastography (Fibroscan®), followed by the NAFLD fibrosis score (49%). For FIB-4, 71% of respondents used a low cut-off of 7.5 to >20 kPa, respectively). Conclusions: The cut-offs used for the same NITs for NAFLD risk stratification vary between clinicians. As cut-offs impact test performance, these findings underscore the heterogeneity in risk-assessment and support the importance of establishing consistent guidelines on the standardised use of NITs in NAFLD management. Lay summary: Owing to the high prevalence of non-alcoholic fatty liver disease (NAFLD) in the general population it is important to identify those who have more advanced stages of liver fibrosis, so that they can be properly treated. Non-invasive tests (NITs) provide a practical way to assess fibrosis risk in patients. However, we found that the cut-offs used for the same NITs vary between clinicians. As cut-offs impact test performance, these findings highlight the importance of establishing consistent guidelines on the standardised use of NITs to optimise clinical management of NAFLD.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; ALERJİ; GASTROENTEROLOJİ VE HEPATOLOJİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; ALLERGY; GASTROENTEROLOGY & HEPATOLOGY; MEDICINE, GENERAL & INTERNAL; Dahiliye; İmmünoloji ve Alerji; Hepatoloji; Gastroenteroloji; Internal Medicine; Immunology and Allergy; Hepatology; Gastroenterology; Elastography; FIB-4; NAFLD; NFS; NITs